Colombia : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 1999)
This 1999 Article IV Consultation highlights that the recession in Colombia intensified in 1999. The unemployment rate rose to a record 20 percent in September, while inflation fell to 9 1\2 percent and the current account deficit came down sharply. The fiscal position deteriorated markedly during the first half of 1999, largely as a result of weak tax collections and higher outlays on interests, wages, and pensions. As market sentiment toward Colombia remained unfavorable, the peso came under repeated pressure, and on September 27, 1999, the central bank allowed the currency to float.